UN MODELO PROBABILÍSTICO PARA LA MORTALIDAD EN LA INFANCIA EN UNA FAMILIA - Pandey, Himanshu; Kishun, Jai (Revista Colombiana de Estadística, 2010)
This paper proposed, under assumptions of inflated type fixed displaced geometric model, the distribution pattern of families according to number of child deaths within the first five years of life. The proposed model involves several parameters related to child mortality in a family, which is estimated with Method of Moments and Maximum Likelihood Estimation techniques. The proposed models fitted the observed data showing a better approximation at the survey area and draw some vital conclusions.